2022
DOI: 10.1172/jci147908
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NANOG/HDAC1 axis reverses resistance to PD-1 blockade by reinvigorating the antitumor immunity cycle

Abstract: Immune checkpoint blockade (ICB) therapy has shifted the paradigm for cancer treatment.However, the majority of patients lack effective responses due to the emergence of immune-refractory tumors that disrupt the amplification of anti-tumor immunity. Therefore, identifying clinically available targets that restrict anti-tumor immunity is required to develop potential combination strategies. Here, using the transcriptome data of cancer patients treated with programmed cell death protein-1 (PD-1) therapy, and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Since an increase of autophagosome abundance could trigger the secretion of intracellular molecule 39 , we first investigated secretion levels of EGFR ligands. Previous studies indicated that EGFR activation is mediated by EGF and its related ligands, and that increased phosphorylation of EGFR through the autocrine growth factor loop plays an important role in human cancers 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Since an increase of autophagosome abundance could trigger the secretion of intracellular molecule 39 , we first investigated secretion levels of EGFR ligands. Previous studies indicated that EGFR activation is mediated by EGF and its related ligands, and that increased phosphorylation of EGFR through the autocrine growth factor loop plays an important role in human cancers 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor impact of CD8 + T cells can be improved directly by promoting CD8 + T cell proliferation and activation in order to restore CD8 + T cell antitumor activity. (2) Enhance the antitumor effect of CD8 + T cells indirectly, that is, dasatinib [120], PD-L1 inhibitors [121][122][123], ginseng-derived nanoparticles (GDNPs) [124], 5-fluorouracil, oxaliplatin [125], LAG-3 inhibitors [126], anti-OX40 agonists [127], STAT [128], Escherichia coli-derived monophosphoryl lipid A [129], CD40 inhibitors [130], phenolic immunogenic cell death nanoinducers [131], IL-17A inhibitors [132], NANOG/HDAC1 axis inhibitors [133], and so on. CD8 + T cell enhancement has an indirect anti-tumour effect by inhibiting Treg cells and promoting DC maturation to improve CD8 + T cell infiltration.…”
Section: Pd-1 Combination Therapymentioning
confidence: 99%
“…Using the transcriptional data obtained from cancer patients treated with PD-1 therapy and a newly established murine preclinical anti-PD-1 therapy-refractory model, NANOG was identified as a factor that enhanced patients’ resistance to immune-checkpoint inhibitors. NANOG regulated this immune checkpoint by suppressing T-cell infiltration and increasing resistance to killing by cytotoxic T lymphocytes (CTLs) through a histone deacetylase 1-dependent (HDAC1-dependent) regulation of CXCL10 and MCL1 [ 31 ].…”
Section: Roles Of Nanog In Cancer Cellsmentioning
confidence: 99%